Mapping Area of Nagari Tanjung Gadang Sijunjung Regency - Yenni Kurniawati; Dina Fitria; Admi Salma (Pelita Eksakta, 2025)
Developing a digital village as a government point of view supports Nagari Tanjung Gadang as one of Sicantik (a village loving statistics). The village and server got the up to date data about the village and its sub-village. The problem for the village is presenting and analysing the data to publish as it is used. They also found difficulties in writing it into a publication format. The server gave an assistance to write Lumbuang Data Nagari Tanjung Gadang. The result is a book which explains the demographic condition of the village.